Continuous UV‐Flow Microsystem for Efficient Radical Generation from Organotrifluoroborates by Photoredox Catalysis. Issue 25 (15th August 2016) - El Achi, Nassim; Penhoat, Maël; Bakkour, Youssef; Rolando, Christian; Chausset‐Boissarie, Laëtitia
Abstract : An efficient continuous‐flow protocol for C–O and C–C bond formation from organoborates by photoredox catalysis under UV irradiation was explored. The combination of a cyclometalated iridium photocatalyst, high‐power UV light‐emitting diode irradiation, and microreactor technology resulted in very efficient radical generation. The flow device enabled determination of highly accurate kinetic data that allowed the observation of good correlations with the standard Hammett σ (–0.26 to 0.227) values for a wide variety of substituents on the benzyl moiety ( ϱ = –4.70, R 2 = 0.98). Good to excellent yields were obtained for a variety of substrates by applying significantly short residence times. Abstract : A continuous‐flow protocol for C–O/C–C bond formation from organoborates by photoredox catalysis under UV irradiation is presented. The combination of a cyclometalated iridium photocatalyst and high‐power (HP) UV light‐emitting diodes (LEDs) with a simple microreactor results in radical generation with yields similar to those of the known batch procedure but with remarkably shorter reaction times.